HUBUNGAN PEMBENTUKAN KARAKTER DI KELUARGA DAN DI SEKOLAH DENGAN PRESTASI BELAJAR ANAK DI SEKOLAH DASAR BERBASIS AGAMA KATOLIK DAN PROTESTAS DI KOTA MEDAN - SITANGGANG, MEGALAS MARIA (Unversitas Katolik Santo Thomas, 2019)
This research is aimed to know the correlation of the Character Building in Family and School to the Child’s Learning Achievement at the Elementary School Based on the Catholics and Protestant Religion in the City of Medan. This is a correlation research using quantitative approach. The population used in this research are grades four and five pupils of the elementary school based on Catholic and Protestant religion in the city of Medan with the total of six hundred pupils. The sampling quota was used in sampling process. Datas in this research were obtained by using character building questionnaire in families and school. The analysis technique in this research is using Statistic Program For Social Science (SPSS) ver. 22. The result of the research showed that to build the character of the pupils in the families and school with its correlation to the learning achievement, the following should be considered: parents do not tell lies in front of their children, teachers should cut the students’ marks if they are late in collecting their assignments and punish them when they do not do their homework.